My half of the sky : 12 life stories of courage - Raimedhi, Indrani, 1963- (SAGE, 2014)
The 12 women who feature in this book come from diverse backgrounds. The thread that binds their stories is their resolve to change the circumstances of their lives, overcoming tremendous odds, and giving wings to their dreams. They are survivors and pathfinders, doers and dreamers, leaving in their wake surging inspiration and hope. Their testimonies reveal what it is to live in this often forgotten corner of India. They have overcome personal tragedy, broken the falters of tradition, discrimination, and coped bravely with the harrowing experience of violence and uncertainty.